2019
DOI: 10.1111/vcp.12736
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors associated with Ehrlichia canis in a hospital canine population

Abstract: Ehrlichia canis (E canis) is the principal cause of canine monocytic ehrlichiosis (CME) and the only Ehrlichia spp that has been identified in the dogs of Europe. 1 Clinical recovery is the expected outcome of acutely infected dogs entering the subclinical phase, which could last several months to years; however, an unpredictable proportion of dogs will eventually develop the chronic phase, typically characterized by aplastic pancytopenia and a high mortality. 2 Fever, depression, anorexia, lymphadenomegaly, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(55 reference statements)
0
3
1
2
Order By: Relevance
“…A study with 73 dogs in Thailand found that the frequency of hematocrit values <15% was significantly higher in those infected with E. canis (31%) compared to those without infection (5.9%) ( p < 0.05) [ 38 ]. However, none of these studies detailed the differences in thrombocytopenia or other parameters by sex of the dogs [ 32 , 37 ], and we found in the present study that thrombocytopenia was significantly higher among infected male dogs (75%) than in non-infected males (20%).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…A study with 73 dogs in Thailand found that the frequency of hematocrit values <15% was significantly higher in those infected with E. canis (31%) compared to those without infection (5.9%) ( p < 0.05) [ 38 ]. However, none of these studies detailed the differences in thrombocytopenia or other parameters by sex of the dogs [ 32 , 37 ], and we found in the present study that thrombocytopenia was significantly higher among infected male dogs (75%) than in non-infected males (20%).…”
Section: Discussioncontrasting
confidence: 73%
“…Another study in Greece, retrospective, assessing medical records of 850 client-owned dogs, found that thrombocytopenia was significantly higher (66%) among those with positive anti- E. canis IgG antibodies, compared to those negative (38%) ( p < 0.0001) [ 32 ]. In addition, anaemia and pancytopenia (57% and 8%) were significantly higher among those infected than in those free of the pathogen (36% and 3%, respectively) ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Essa incidência também pode variar em relação ao sexo do animal, como descrito em outros estudos, já que esses animais costumam ter o hábito de serem semidomiciliados e aumenta-se o risco de se tornarem infectados (ZUCHI et al, 2020;COSTA JR et al, 2007). (1,2429 -2,8534) Tabela 1: Fatores de riscos associados com a soropositividade por Erlichia canis no município de Floriano-PI Apesar de ser observado em diferentes estudos que a idade adulta e a raça dos cães estão relacionadas como fatores de risco para erliquiose canina, como observado por Piantedosi et al (2019) e Chochlios et al (2019), no presente estudo não foi observado nenhum desses fatores como um fator de risco (Tabela 1). Sugere-se que foram observados esses resultados devido a reduzida taxa de animais semidomiciliados no estudo.…”
Section: Resultsunclassified
“…Essa incidência também pode variar em relação ao sexo do animal, como descrito em outros estudos, já que esses animais costumam ter o hábito de serem semidomiciliados e aumenta-se o risco de se tornarem infectados (ZUCHI et al, 2020;COSTA JR et al, 2007). Apesar de ser observado em diferentes estudos que a idade adulta e a raça dos cães estão relacionadas como fatores de risco para erliquiose canina, como observado por Piantedosi et al (2019) e Chochlios et al (2019), no presente estudo não foi observado nenhum desses fatores como um fator de risco (Tabela 1). Sugere-se que foram observados esses resultados devido a reduzida taxa de animais semidomiciliados no estudo.…”
Section: Resultsunclassified